2019
DOI: 10.1002/celc.201900343
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen/Cobalt Co‐doped Mesoporous Carbon Microspheres Derived from Amorphous Metal‐Organic Frameworks as a Catalyst for the Oxygen Reduction Reaction in Both Alkaline and Acidic Electrolytes

Abstract: Nitrogen/cobalt co-doped carbon (Co/NÀ C) catalysts are the best candidates to replace their Fe-based analogues for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs), owing to the absence of radical-induced PEMFC membrane/ionomer degradations that are commonly encountered in the Fe/NÀ C system. Herein, we present an amorphous Co-metal organic framework (MOF) route for the fabrication of N/Co co-doped mesoporous carbon spheres by directly pyrolyzing amorphous Co-MOF microsphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Additionally, we have made an attempt to explore another aspect of the ORR polarization curve, especially the adversity associated with catalytic poisoning and the concomitant possible situation with regards to FC performance as various studies emphasize developing electrocatalysts tolerant to poisoning. Generally, reagents such as NaCN, NaSCN, CO, KCN, and H 2 S have the potential to poison the metal-based active centers. ,, In general, the reduction of J d in LSV-RDE ORR polarization curves and the comparative negative shift (i.e., increased overpotential) in E onset are considered to be fingerprints of the poisoning effect. ,, However, the issue of how the poisoning of an electrocatalyst may cause a grim situation for FC operation should be realized and addressed, which will be helpful in developing poison-tolerant electrocatalysts, especially from an ORR perspective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have made an attempt to explore another aspect of the ORR polarization curve, especially the adversity associated with catalytic poisoning and the concomitant possible situation with regards to FC performance as various studies emphasize developing electrocatalysts tolerant to poisoning. Generally, reagents such as NaCN, NaSCN, CO, KCN, and H 2 S have the potential to poison the metal-based active centers. ,, In general, the reduction of J d in LSV-RDE ORR polarization curves and the comparative negative shift (i.e., increased overpotential) in E onset are considered to be fingerprints of the poisoning effect. ,, However, the issue of how the poisoning of an electrocatalyst may cause a grim situation for FC operation should be realized and addressed, which will be helpful in developing poison-tolerant electrocatalysts, especially from an ORR perspective.…”
Section: Resultsmentioning
confidence: 99%
“…In the last two decades, the immense growth in the development and design of ecofriendly sustainable energy devices has driven a large number of researchers across the globe (in either developed or developing nations) to find, develop, and design robust and effective oxygen electrocatalysts. This is obvious from the increase of scientific journals and publications across the publishing houses (Figure ). A careful observation of already published scientific contributions suggests that, in a large fraction of the literature, ORR studies (with matrices like E onset , E 1/2 , and high J d ) have been carried out to claim better prospective oxygen electrocatalysts (Figure a). ,, In all of these scientific contributions, authors have concluded that the electrocatalysts are suitable for electrochemical devices such as FCs and MABs based on ORR parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this catalyst presented the highest I D / I G value (≈1.52) among all the materials investigated, which is crucial to ensure fast electron transfer. In alkaline media ( Figure 11 ), the mesoporous carbon microspheres prepared by Bai et al [ 98 ] showed the best ORR activity in the Co-based catalyst category. Although the BET surface area was not very high (381 m 2 g − ), this catalyst had a high pore volume of 1.25 cm 3 g −1 and a low micropore surface area (14.8 m 2 g −1 ), thus being a typical mesoporous material.…”
Section: Discussionmentioning
confidence: 99%
“…N/Co-co-doped mesoporous carbon microspheres were synthesized by solvothermal treatment of a 3,6-bis(1-imidazolyl)-1,2,4,5-tetrazine (BIMT) linker with Co(II) nitrate followed by pyrolysis at 800 °C under N 2 [ 98 ]. The above linker was selected because tetrazine/imidazole-containing precursors are more inclined to be transformed into graphitic- and pyridinic-N species, which are active catalytic sites for the ORR.…”
Section: Mof-based Orr Electrocatalystsmentioning
confidence: 99%
“…11,12 Furthermore, metal N-doped carbons (M-N-C), specifically cobalt-based N-doped carbons (Co-N-C) have attracted extensive attention as suitable multifunctional catalysts. [13][14][15][16][17][18] Their high catalytic activity, originating from the strong coupling effect of Co with N, leads to the formation of active sites with suitable binding energies for promoting the discharging and charging reactions. 6 Cobalt may also promote the catalytic graphitization of amorphous carbon, 17,19,20 however it has been challenging to prepare catalysts with relatively well dispersed cobalt-based nanoparticles on the graphitic carbon network, which is essential to promote even transport of electrons to the Co-based active sites and hence rate of reaction across the catalyst framework.…”
Section: Introductionmentioning
confidence: 99%